Enhancing 21st Century Skills through Sustainable Inorganic Chemistry Teaching Materials Development from Recycled Materials: Integrating SDGs in Chemistry Learning Media - Marfu’ah, Siti; Farwati, Ratna; Meristin, Annisa; Franzizko, Dimi A.; Putri, Pelangi A. E.; Wardani, Farach E. (Proceeding International Conference on Religion, Science and Education, 2025)
The development of effective and sustainable teaching materials for inorganic chemistry presents a significant challenge in higher education, especially considering resource limitations and the need to integrate sustainability principles. This study aims to analyze the creativity of students in developing inorganic chemistry learning media based on recycled materials, as well as to explore the integration of Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action). A total of 26 students enrolled in the Chemistry Learning Media course over one semester participated in this project. A descriptive qualitative method with a case study approach was employed in this research. The process consisted of four main stages: project orientation, media development, presentation and evaluation, and reflection. Data were collected through observations, documentation, interviews, and product assessments. The findings indicate that students successfully created chemistry learning media with high levels of creativity and complexity using recycled materials such as cardboard, plastic bottle caps, marbles, and used LEDs, representing various inorganic chemistry concepts. This project also contributed positively to students’ understanding of chemical concepts, development of 21st-century skills (such as creativity, innovation, collaboration, communication, and problem-solving), and increased awareness of environmental and sustainability issues. These findings highlight the importance of developing innovative and eco-friendly learning media as part of sustainable educational practices in higher education.